DIALOG DAN KERUKUNAN UMAT BERAGAMA DI INDONESIA DALAM PEMIKIRAN A. MUKTI ALI - Moh. khairul Fatih (UIN Sunan Kalijaga Yogyakarta, 2017)
Indonesia as a pluralistic country inherited the spirit of tolerance, peace and recognize religious pluralism and unity of truth as a form tantularisme, the religious fervor that has a religious typology, non-doctrinaire, tolerant, accommodating and optimistic. To achieve harmony among religious believers in Indonesia, every religious followers should understand and respect the religious beliefs of different shapes. There are five concepts of thought offered by Mukti Ali to respect religious diversity and creating a harmonious: syncretism, reconception, Synthesis, replacement, and agree in disagreement. The fifth concept is realized in the form of dialogue as a means of forming harmony. Inter-religious dialogue is the means used Mukti Ali in his efforts to form unity. Dialogue and harmony among religious believers is a bridge that can not be separated, both will be interrelated because in the quest for harmony be required also inter-religious dialogue as a means of dialogue, friendship and cooperation in creating an ideal social order.